(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Having defined the fundamental characteristics of limpieza social, the systematic killing of marginal subjects in Colombia, this research explores the role played by the State in the preparation of favorable conditions for the development, legitimacy, and maintenance of the practice. It analyzes the fundamental attributes of the extreme violence that social cleansing expresses. The study tries to understand this phenomenon by examining the connection between sovereignty, delimitation of political space, borders, human rights, and citizenship